The commitment engine : making work worth it - Jantsch, John. (New York : Portfolio/Penguin, 2012)
Reveals the secrets of companies who have inspired loyalty in customers and employees, demonstrating the importance of a single-minded company purpose while providing coverage of such topics as strategy, culture, and customer promise.
Includes index.
Keywords: Customer loyalty; Corporate culture; Organizational behavior; Commitment (Psychology).